Fluoroscopy-guided aspiration of the acutely dislocated total hip arthroplasty: a feasible, high-yield, and safe procedure - Dyan V. Flores; Abdullah Felemban; Taryn Hodgdon; Paul Beaulé; George Grammatopoulos; Kawan S. Rakhra (Insights into Imaging)
Abstract Objective To determine the feasibility, yield, and safety of fluoroscopic-guided aspiration of the acutely dislocated total hip arthroplasty (AD-THA). Materials and methods IRB-approved, retrospective review of fluoroscopic-guided aspirations of AD-THA (January 2005–December 2023) was performed. Data from electronic charts and fluoroscopy images/reports were obtained. Positive yield was defined as spontaneous aspirate or saline rinse adequate for microbiology analysis. Sub-analysis by needle target (acetabular cup or femur) was performed for spontaneous aspiration rate, aspirate volume and fluoroscopy time. Differences between groups were analyzed with unpaired, t-test (2-tail) and between proportions with Fisher’s exact test, with significance p < 0.05. Results Aspiration of 20 AD-THA in 19 patients (12 female, mean age (SD) of 73 years (16)) targeted the acetabular cup in 45% (9/20) or femur in 55% (11/20) of cases. Positive yield was obtained in 95% (19/20), with spontaneous aspirate in 75% (15/20) and saline rinse in 20% (4/20) of cases; in 5% (1/20), no diagnostic sample was obtained. Spontaneous aspirate mean volume (SD, range) for all cases was 8.3 mL (6.9, 0.2–25), and higher when targeting the acetabular cup 11.2 mL (6.9, 5–25) versus the femur 4.0 mL (4.4, 0.2–12) (p = 0.026). The rate of spontaneous aspiration was higher for the acetabular cup 100% (9/9) versus the femur 55% (6/11) (p = 0.038). The mean fluoroscopy time (SD, range) for all cases was 43 s (25, 19–102), and shorter for targeting the acetabular cup 32 s (16, 19–75) versus the femur 56 s (28, 28–102) (p = 0.034). No immediate complications occurred in all aspirations. Conclusion Fluoroscopy-guided aspiration of AD-THA is a feasible, high-yield, and safe procedure. Targeting the acetabular cup results in a higher rate of spontaneous aspirate, larger aspiration volume, and lower fluoroscopy time. Critical relevance statement Although technically more challenging, radiologists should feel confident aspirating the acutely dislocated total hip arthroplasty (AD-THA) under fluoroscopic guidance. Key Points Total hip arthroplasty (THA) infection can be evaluated with synovial fluid aspiration. Fluoroscopic-guided aspiration of the dislocated THA is feasible, high-yield, and safe. Targeting of the acetabular cup is recommended over the femoral prosthetic component. Acetabular cup targeting gives larger, spontaneous aspirates with lower fluoroscopy time. Graphical Abstract